Asthma, allergies and respiratory symptoms in different activity groups of swimmers exercising in swimming halls - Päivinen, M., Keskinen, K.; Putus, T.; Kujala, U. M.; Kalliokoski, P.; Tikkanen, H. O. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background Respiratory symptoms are common in competitive swimmers. However, among these and in swimmers at other activity levels the swimming distance, the total spent time in swimming halls and their medical background varies. Our objectives were, first, to assess their medical histories and the associations with respiratory symptoms among swimmers in different activity groups and then second, to study the pulmonary function findings and related medications in competitive swimmers who exercise in swimming hall environments the most.